Exploring Christian theology : the church, spiritual growth, and the end times - Holsteen, Nathan D.; Svigel, Michael J., 1973- (Bethany House Publishing ; Minneapolis, 2014)
"Dallas Theological Seminary professors make basic theology accessible for everyone. Included are key doctrines on the church, spiritual growth, and the end times"--
Includes bibliographical references (pages 231-236) and index.
Keywords: Church; Eschatology; Spiritual formation; Theology, Doctrinal